An economic assessment of SO2 reduction from industrial sources on the highveld of South Africa - Steyn, Marilize; Kornelius, Gerrit (Clean Air Journal, 2018)
The costs and benefits associated with the implementation of an SO2 point source standard for solid fuel combustion installations (Category 1.1 sources, National Environmental Management: Air Quality Act: s21 List of Activities 2013) were evaluated to assess the desirability of implementation of the standards from an environmental as well as economic point of view. The study used a bottoms-up or impact pathway approach to analyse the impact of emission reduction. To reach the new plant (2020) SO2 emission standard of 500 mg/Nm3, the installation of wet flue gas desulfurisation (FGD) is the likely technology as it is a widely installed and well-developed technology. Costs and benefits associated with the installation of FGD were identified and ranked into four categories, based on the expected impact and the availability of information. All costs and benefits that could be quantified and monetized (Category 1 impacts) were included in the evaluation. A sensitivity analysis was conducted on the costs and benefits with the largest impact on NPV (net present value) or the largest uncertainty associated with the calculation to determine a range of feasible values. Site specific information was used where available, supplemented by benefit transfer where local data was not available. The impact on premature adult mortality was found to be the most significant benefit and dependent on the concentration response function selected and sensitive to the VSL (value of statistical life) estimate used (high R115 billion; low R36 billion). The choice of appropriate concentration response functions and the applicability thereof in the South African context are important considerations, likely requiring further study. The capital cost of FGD installations was found to be the most significant cost and was sensitive to the evaluation method (central R187 bil; high R306 bil; low R80 bil). Failure to account for operating costs would significantly impact the economic evaluation. The results of the study indicate that, given the information currently available, it is unlikely that the benefit of reducing SO2 emissions from existing sources to the required standard outweighs the cost of implementation on the Mpumalanga Highveld.